2019
DOI: 10.1016/j.biopsych.2019.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Habituation Learning Is a Widely Affected Mechanism in Drosophila Models of Intellectual Disability and Autism Spectrum Disorders

Abstract: BACKGROUND: Although habituation is one of the most ancient and fundamental forms of learning, its regulators and its relevance for human disease are poorly understood. METHODS: We manipulated the orthologs of 286 genes implicated in intellectual disability (ID) with or without comorbid autism spectrum disorder (ASD) specifically in Drosophila neurons, and we tested these models in light-off jump habituation. We dissected neuronal substrates underlying the identified habituation deficits and integrated genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(80 citation statements)
references
References 66 publications
5
71
0
Order By: Relevance
“…We found that the vast majority of strains with mutations in ASD-associated genes displayed delayed development or growth impediments, a finding consistent with a recent large-scale analysis of inactivating mutations in constrained genes in humans (69). We also found that a large number of ASD-associated genes impair habituation, a finding consistent with a recently reported largescale analysis of ASD-and intellectual disability/developmental delay-associated genes in Drosophila and humans (70). Interestingly, our data show that ASD-associated genes specifically impair habituation of response probability.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found that the vast majority of strains with mutations in ASD-associated genes displayed delayed development or growth impediments, a finding consistent with a recent large-scale analysis of inactivating mutations in constrained genes in humans (69). We also found that a large number of ASD-associated genes impair habituation, a finding consistent with a recently reported largescale analysis of ASD-and intellectual disability/developmental delay-associated genes in Drosophila and humans (70). Interestingly, our data show that ASD-associated genes specifically impair habituation of response probability.…”
Section: Discussionsupporting
confidence: 90%
“…The results also provide a potentially plausible explanation for inconsistent reports of impaired habituation in humans, which variably employ diverse response metrics most often without genetic stratification of patient populations (15,39). While these shared phenotypes are exciting, our results and those of several other model systems (11,15,19,22,70,71) reveal a remarkable diversity in phenotypic disruptions, suggesting that single phenotype functional validation and characterization efforts will be insufficient to capture the complex multifaceted phenotypic disruptions that stem from mutations in ASD-associated genes.…”
Section: Discussionmentioning
confidence: 84%
“…Auditory paradigms, in general, lend themselves to being used translationally with a wide range of species (both asleep and awake) due to the passive nature of the task. Non-human animal models have been AUDITORY PROCESSING IN INFANTS WITH NEUROFIBROMATOSIS TYPE I particularly informative in NF1 research (Costa et al, 2002;Fenckova, Blok, Asztalos, Goodman, Cizek, Singgih, Glennon, IntHout, Zweier, Eichler, von Reyn, et al, 2019;Gonçalves et al, 2017;Shilyansky et al, 2010), demonstrating impairments in attention, habituation, motor co-ordination and visual-spatial learning. As the sensory systems are tightly coupled, and research has well established the modulatory effect of attention on sensory processing (Näätänen, 1990;Woldorff et al, 1993), this may be a fruitful avenue of further research when investigating NF1.…”
Section: Change Detectionmentioning
confidence: 99%
“…More importantly, these early differences have been associated with downstream effects on social and non-social sound processing and language production (Eigsti & Fein, 2013;Homae et al, 2012;Yu et al, 2015). Taken together, auditory habituation and deviance detection could provide important insights into basic perceptual processing in infants with NF1, and help us understand whether disrupted low-level auditory processing is predictive of ASD diagnosis in toddlerhood or appear as a cumulative risk factor across several neurodevelopmental conditions (Fenckova, Blok, Asztalos, Goodman, Cizek, Singgih, Glennon, IntHout, Zweier, Eichler, Reyn, et al, 2019;Guiraud et al, 2011;Knoth et al, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation